IMPLEMENTASI KEBIJAKAN PEMBERANTASAN PENYAKIT DBD (DEMAM BERDARAH DENGUE) DI KOTA PEKANBARU - Rahma Hayati Br Tarigan; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
DHF (Dengue Hemorrhagic Fever) is a contagious disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito, which is characterized by sudden fever for 2-7 days without a clear cause accompanied by weakness / lethargy, restlessness, heartburn accompanied by signs on the skin in the form of red spots, bruises (echymosis) or rash (purpura). Pekanbaru City is the region with the highest DHF (Dengue Hemorrhagic Fever) rate in Riau Province. The Pekanbaru City Government itself through the Pekanbaru City Health Office and Cross sectors continues to strive to eradicate this disease. Efforts to eradicate DHF (Dengue Hemorrhagic Fever) are described in the Decree of the Minister of Health of the Republic of Indonesia Number 581 / Menkes / SK / VII / 1992 concerning the Eradication of Dengue Hemorrhagic Fever. The purpose of this study was to determine how the implementation of the DHF (Dengue Fever) Eradication Policy in Pekanbaru City and its inhibiting factors. This research uses a case study method with a descriptive qualitative approach. Cases and data required both primary data and secondary data obtained through observation, interviews and documentation then analyzed based on research problems. The results of this study indicate that the implementation of Dengue Hemorrhagic Fever (Dengue) Eradication Policy in Pekanbaru City has not been going well with inhibiting factors, namely Resources, Commitment of implementing agents, Communication and Coordination. Keywords: Implementation, Eradication, DHF (Dengue Hemorrhagic Fever)